Answering More of the Same: A Reply to Nahm - Augustine, Keith (Journal of Scientific Exploration, 2023)
Nahm’s preceding commentary accuses me of seven misrepresentations. One of these is an acknowledged good-faith error about a peripheral detail, while the remaining six are demonstrably accurate descriptions of Nahm’s statements. At the same time, Nahm verifiably misrepresents me frequently and intentionally over issues that he takes to be consequential, which is a much more serious offense. All authors should call out when an interlocutor get their points wrong, but only when they can definitively back up the charge. Where Nahm weakly attempts to show that I misrepresented him, I will show that, if anything, his showcase consists of six verifiably accurate characterizations of his Bigelow Institute contest-winning essay’s conclusions. His commentary exemplifies the truism that one can appeal to a million frivolous reasons to dismiss what an opponent has to say if one is absolutely determined not to hear him. Though committed survivalists will undoubtedly be satisfied that survival researchers have responded to me regardless of whether they have responded well, those that care about the underlying issues will hopefully find value in my reply.